Kajian Kualitas Sistem Informasi Manajemen Sales Colony Terhadap Tingkat Penerimaan Dan Tingkat Kepuasan Pengguna Akhir : Studi Kasus Pada ABC Bank - Iskandar, Rudy Sugiharto; Sensuse, Dana Indra (Lembaga Penerbitan Universitas Esa Unggul, 2008)
The use of advance technology that is able to speed business activities in an organization is desperately needed nowdays. The success of new technology implementation depends on quality of the technology, either,Ã‚Â quality of system design, quality of information presented, or quality of the service provided, which determine the level of revenue and the level of end-user satisfaction. Entering the end of 2006, a divizion of ABC Bank, namely Sales Colony, which moves into the card sale payment has started applying a kind of management information system called the Sales Colony Management System (SCMS). The SCMS is one example of the new IT application applied, which aims to accelerate the process of business activities that, viewed in terms of speed, effectiveness and efficiency. Result of the study shows that there was a significant correlation between high quality information system SCMS with the level of revenues, and the level of end-user satisfaction, where the better quality information system SCMS, the higher the level of acceptance and satisfaction of end users to the system. Many benefits and convenience of the system of information SCMS are seen. The factors that mostly affect the end-user satisfaction in the use of the information system is the quality of the information presented, the quality ofÃ‚Â perceived ease of use, the quality ofÃ‚Â service of theÃ‚Â IT Colony sales staff .Keywords: Quality, Management Information System, SCMS